Exploring the role of Fusobacterium nucleatum in colorectal cancer: implications for tumor proliferation and chemoresistance - Leila Dadgar-Zankbar; Zahra Elahi; Aref Shariati; Azad Khaledi; Shabnam Razavi; Amin Khoshbayan (Cell Communication and Signaling)
Abstract Fusobacterium nucleatum (Fn) has been extensively studied for its connection to colorectal cancer (CRC) and its potential role in chemotherapy resistance. Studies indicate that Fn is commonly found in CRC tissues and is associated with unfavorable prognosis and treatment failure. It has been shown that Fn promotes chemoresistance by affecting autophagy, a cellular process that helps cells survive under stressful conditions. Additionally, Fn targets specific signaling pathways that activate particular microRNAs and modulate the response to chemotherapy. Understanding the current molecular mechanisms and investigating the importance of Fn-inducing chemoresistance could provide valuable insights for developing novel therapies. This review surveys the role of Fn in tumor proliferation, metastasis, and chemoresistance in CRC, focusing on its effects on the tumor microenvironment, gene expression, and resistance to conventional chemotherapy drugs. It also discusses the therapeutic implications of targeting Fn in CRC treatment and highlights the need for further research.